Development of a robotic arm-based deorbiter CubeSat to capture co-operative space debris in LEO - Laveneishyan, B Mogan (Nanyang Technological University, 2021)
The report is written to summarize the final year project's concepts, designs, methodologies, and data. This final year project report provides a fundamental understanding of the working principle of robotics arm in of a Cube Satellite (CubeSat) and the detailed explanation of capturing process a space debris in orbit. The type of capturing system chosen for this satellite project is robotics arm control system which is ideal for cooperative space debris. This robotics arm capturing system is designed to capture X-Sat, a CubeSat which is developed and launched by Satellite Research Centre at Nanyang Technological University.